DEVELOPMENT OF VIDEO TUTORIAL LEARNING MEDIA FOR STUDENTS AT UNIVERSITAS MUHAMMADIYAH SUKABUMI - Al Afiah, Ferdiansyah Ulul Azmi; Yudianto, Arif; Maharani, Isma Nastiti (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2020)
AbstractThis study aims to develop a video tutorial media design that will be used as a learning medium and test the feasibility of the resulting product. This research is a development research with development procedures according to Borg and Gall stages such as 1) Potential and Problems, 2) Data Collection, 3) Product Design, 4) Design Validation, 5) Design Revision, 6) Product Testing, 7) Product Revision, 8) Trial Use, and 9) Product Revisions. The research subjects were students of Information Technology Education at Muhammadiyah Sukabumi of University. The object of this research is the development of instructional media for video tutorials on shooting techniques and camera movement. Data collection to determine the assessment of material experts, media experts and students of this tutorial video learning media using a Likert type questionnaire with a score range of 1 to 5. Based on the evaluation of material experts by 91%, media experts by 95% and students by 88% who included in the very feasible category, this video tutorial learning media is suitable for use as a learning medium in videography courses at the Information Technology Education, Muhammadiyah University of Sukabumi. Keywords: learning media, videography, video tutorialsDOI: http://dx.doi.org/10.23960/jpvti.v2.i2.202002